2020
DOI: 10.1038/s41380-020-0821-6
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of functional and structural plasticity of dendritic spines during NMDAR and mGluR-dependent long-term synaptic depression in wild-type and fragile X model mice

Abstract: Many neurodevelopmental disorders are characterized by impaired functional synaptic plasticity and abnormal dendritic spine morphology, but little is known about how these are related. Previous work in the Fmr1-/y mouse model of fragile X (FX) suggests that increased constitutive dendritic protein synthesis yields exaggerated mGluR5-dependent long-term synaptic depression (LTD) in area CA1 of the hippocampus, but an effect on spine structural plasticity remains to be determined. In the current study, we used s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 75 publications
(121 reference statements)
1
37
0
Order By: Relevance
“…Ion-flow-independent NMDAR signaling has been implicated by many independent studies in spine shrinkage and synaptic weakening ( Aow et al, 2015 ; Birnbaum et al, 2015 ; Carter and Jahr, 2016 ; Nabavi et al, 2013 ; Stein et al, 2015 , 2020 ; Thomazeau et al, 2020 ; Wong and Gray, 2018 ). Here, we made the unexpected discovery that this non-ionotropic NMDAR signaling pathway is also required for spine growth during synaptic strengthening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ion-flow-independent NMDAR signaling has been implicated by many independent studies in spine shrinkage and synaptic weakening ( Aow et al, 2015 ; Birnbaum et al, 2015 ; Carter and Jahr, 2016 ; Nabavi et al, 2013 ; Stein et al, 2015 , 2020 ; Thomazeau et al, 2020 ; Wong and Gray, 2018 ). Here, we made the unexpected discovery that this non-ionotropic NMDAR signaling pathway is also required for spine growth during synaptic strengthening.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that LTD ( Carter and Jahr, 2016 ; Nabavi et al, 2013 ; Wong and Gray, 2018 ) and dendritic spine shrinkage ( Birnbaum et al, 2015 ; Stein et al, 2015 ; Thomazeau et al, 2020 ) can occur independent of ion flux through the NMDAR. These findings have supported a model in which glutamate binding leads to conformational changes in the NMDAR that drive spine shrinkage and synaptic weakening.…”
Section: Introductionmentioning
confidence: 99%
“…Ion flow-independent NMDAR signaling has been implicated by many independent studies in spine shrinkage and synaptic weakening (Nabavi et al, 2013;Aow et al, 2015;Birnbaum et al, 2015;Stein et al, 2015;Carter and Jahr, 2016;Wong and Gray, 2018;Stein et al, 2020;Thomazeau et al, 2020). Here, we made the unexpected discovery that this non-ionotropic NMDAR signaling pathway is also required for spine growth during synaptic strengthening.…”
Section: Non-ionotropic Nmdar Signaling Drives Bidirectional Spine Stmentioning
confidence: 90%
“…Recent studies have demonstrated that LTD (Nabavi et al, 2013;Carter and Jahr, 2016;Wong and Gray, 2018) and dendritic spine shrinkage (Birnbaum et al, 2015;Stein et al, 2015;Thomazeau et al, 2020) can occur independent of ion flux through the NMDA receptor. These findings have supported a model in which glutamate binding leads to conformational changes in the NMDAR that drive spine shrinkage and synaptic weakening.…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulated glutamate signalling and impaired synapse development have been proposed to contribute to neurodevelopmental and psychiatric disorders. Mutations in NMDAR subunits have been linked to pathogenesis of autism spectrum disorders (ASD), intellectual disability, epilepsy, anxiety, depression and schizophrenia (Endele et al 2010;Hamdan et al 2011;Tarabeux et al 2011;O'Roak et al 2012). Changes in glutamate signalling and aberrant NMDAR expression and function have been observed in the brains of individuals with ASD (Blatt et al 2001;Purcell et al 2001) and in different mouse models of ASD (Etherton et al 2011;Eadie et al 2012;Sceniak et al 2016).…”
Section: The Clinical Relevance Of Prenmdarsmentioning
confidence: 99%